Strategi Komunikasi Pemasaran Terintegrasi PT XYZ Tbk. Tahun 2023-2026 - Iary, Aanisa; Puspita, Anggun Pesona Intan (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
PT XYZ Tbk. is a company that operates in the automotive industry as a company that manufactures fasteners for the B2B market. In recent years, in Indonesia and globally, many phenomena have emerged and been created to increase binder product sales. However, during the last six years, PT XYZ Tbk. has not achieved its sales target even though the automotive sales trend is increasing or stable. Based on interviews, observations, and literature studies that have been conducted, it was found that competitors are more aggressive in communicating their brands and are better known. As a result, the company needs help to intensify sales in global markets and its customer suppliers. This research aims to analyze the role of each integrated marketing communication element for the B2B market and create an integrated marketing communication strategy that has a major impact on achieving sales targets and getting customers. In this study, the analysis uses three perspectives, namely: the company, competitors, and customers. The findings in this study indicate that the integrated marketing communication strategy of PT XYZ Tbk. as a B2B marketer must implement strategies that end with a personal approach to customers and the use of print and digital media to spread wider brand awareness.